Aplikasi Shrinking Core Model Pada Sintesis Hidroksiapatit Menggunakan Metode Hidrotermal Suhu Rendah - Nuraina Siregar; Ahmad Fadli; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite (HA) is a ceramic material can be used as bone and dental implants. Hydroxyapatite can be synthesized from calcium oxide (CaO). The purpose of this study was to determine the effect of reaction time and stirring rate on the characteristics of HA using a low temperature hydrothermal method and determine the kinetics model with the approach of shrinking core models. There are 3 models that are used; diffusion through the film layers, diffusion through the layer result (HA), and chemical reactions. The first procedure was weighing 36.9 of grams NH4H2PO4 and dissolved in 600 ml of aquadest are then added 30 of grams CaO at a temperature of 90 °C and reaction time with variation 5, 30, 60, 90, and 150 minutes. The mixture was stirred rate of 100, 200, 300 rpm until paste formed. The paste was dried in an oven at a temperature of 110oC for 15 hours and calcined at a temperature of 900oC for 1 hour. XRD diffraction results shows HA with pure content of 95% and SEM result shows morphology of HA was like agglomerate. The best kinetics model showed synthesis of HA is model 2 with equation:It was named “Diffusion Through the Layer Results (HA)” with the smallest percentage error of 4,3%.Keywords: CaO, hydroxyapatite, hydrothermal, model kinetics, shrinking core